Characterization of Persistent Volatile Contaminant Sources in the Vadose Zone. Issue 2 (14th February 2013) - Carroll, Kenneth C.; Truex, Michael J.; Brusseau, Mark L.; Parker, Kyle R.; Mackley, Robert D.; Rohay, Virginia J.
Abstract Effective long‐term operation of soil vapor extraction (SVE) systems for cleanup of vadose‐zone sources requires consideration of the likelihood that remediation activities over time will alter the subsurface distribution and configuration of contaminants. A method is demonstrated for locating and characterizing the distribution and nature of persistent volatile organic contaminant (VOC) sources in the vadose zone. The method consists of three components: analysis of existing site and SVE‐operations data, vapor‐phase cyclic contaminant mass‐discharge testing, and short‐term vapor‐phase contaminant mass‐discharge tests conducted in series at multiple locations. Results obtained from the method were used to characterize overall source zone mass‐transfer limitations, source‐strength reductions, potential changes in source‐zone architecture, and the spatial variability and extent of the persistent source(s) for the Department of Energy's Hanford site. The results confirmed a heterogeneous distribution of contaminant mass discharge throughout the vadose zone. Analyses of the mass‐discharge profiles indicate that the remaining contaminant source is coincident with a lower‐permeability unit at the site. Such measurements of source strength and size as obtained herein are needed to determine the impacts of vadose‐zone sources on groundwater contamination and vapor intrusion, and can support evaluation and optimization of the performance of SVE operations.